Vickers Microhardness and Structural Evaluation of Experimental Dental Porcelain With Zirconia Addition - MOLDOVAN, Sorina; MUREȘAN-POP, Marieta; COJAN, Claudia Andreea; BARABÁS, Réka; BIZO, Liliana (Studia Universitatis Babeș-Bolyai Chemia, 2024)
This work aimed to investigate the effect of ZrO2 addition on the structural and mechanical properties of an experimental dental porcelain (DP) prepared from natural raw materials. ZrO2 was added in different amounts (1, 3, and 5 wt.%) to the DP mass with the initial composition of 80 wt.% feldspar, 15 wt.% quartz, and 5 wt.% kaolin, obtained by sintering the mixture at 1200 ºC. The raw materials and raw materials mixture were analyzed by laser diffraction to obtain the typical particle size distribution (PSD). Subsequently, the obtained phases in the elaborated samples were investigated by X-ray powder diffraction (XRPD), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and microhardness tests. The structural analyses revealed that the obtained DP mainly comprised quartz and amorphous phases. In addition, certain peaks of weak corresponding to mullite and zirconia were detected. The measured Vickers microhardness (VMH) of DP sintered at 1200 °C was 794.07±106.56 kgf/mm2, which is comparable with those reported for conventional porcelains. Moreover, ZrO2 addition leads to an overall increase of the VMH, with the best value of 912.91±30.76 kgf/mm2 obtained for the sample with 5 wt.% ZrO2. In conclusion, the DP studied here exhibits good mechanical properties and could be potentially used in restorative dentistry.